2016
DOI: 10.1186/s13104-016-2318-6
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating attitude and associated factors among high school adolescents aged 12–19 years in Addis Ababa, Ethiopia: a cross-sectional study

Abstract: BackgroundEating disorders are very complex, frequently developed and have a public health impact on adolescents. Different studies revealed that eating disorders is a pressing public health problem among adolescents. Eating disorders may also lead to mortality due to their physiological sequelae. There is no previous study regarding disordered of eating attitude in Ethiopian adolescents. Therefore, this study aimed to assess prevalence of disordered eating attitude and its associated factors among adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
2
15
2
1
Order By: Relevance
“…In contrast, the prior Ethiopian study reported a low prevalence of disordered eating attitudes (i.e., about 9% based on the scores of EAT‐26 questioannrie) among male and female adolescents (Yirga et al, ). The main reason for such divergent finding is due to the use of different instruments in measuring disordered eating, and variation in measuring the frequency and duration of behaviors.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, the prior Ethiopian study reported a low prevalence of disordered eating attitudes (i.e., about 9% based on the scores of EAT‐26 questioannrie) among male and female adolescents (Yirga et al, ). The main reason for such divergent finding is due to the use of different instruments in measuring disordered eating, and variation in measuring the frequency and duration of behaviors.…”
Section: Discussionmentioning
confidence: 84%
“…The main reason for such divergent finding is due to the use of different instruments in measuring disordered eating, and variation in measuring the frequency and duration of behaviors. For instance, this study measured the frequency of purging and nonpurging behaviors in the last month, while the prior study measured attitudes related to dieting, bulimia, and oral control on the 6‐point Likert scale (Yirga et al, ). Future reserach is recommended to evaluate the psychometric properties of disordered eating instruments among Ethiopian adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lingkungan sosial ekonomi (Azwar, 2006 #15)k berkaitan dengan kecukupan asupan makanannya. Pendampingan saat makan, suasana rumah yang positif, dan perilaku terkait dengan makanan orang tua yang sesuai sangat berpengaruh terhadap mutu makanan anak (40,41).…”
Section: Pola Pengasuhan Giziunclassified
“…Eating attitudes and behavioural changes may on the one hand lead to the spread of obesity like an epidemic, while on the other hand, the perception of being thin and fit is trigggered (1). Among adolescents and the younger generations in particular there is a desire to be fit or to look thinner, and this can lead to negative nutritional development (2,4) along with such associated diseases as vitamin and mineral deficiencies, anorectic diseases and psychosomatic disorders. Professional groups that often engage in eating and drinking may be affected nutritionally by their profession, leading them to overeat, to refuse to eat or to consume healthy foods.…”
Section: Introductionmentioning
confidence: 99%